FAMILY AND SOCIAL ASPECTS OF CLIENTS IN DRUG ABUSE IN THE REHABILITATION CENTER OF NATIONAL NARCOTIC BOARD - Andi Tilka Muftiah Ridjal; Muhammad Sahlan Zamaa; Irawati, Andi; Syamsuryana; Pangemanan, Alice (Universitas Islam Negeri Alauddin Makassar, 2023)
Family and social lives are the several factors that lead someone to be involved in drug abuse, specifically in children and adults. The United Nations Office on Drugs and Crime (UNODC) noted that in 2021 the number of drug users worldwide was around 275 million in the past year. The National Narcotics Board or Badan Nasional Narkotik (BNN) Baddoka recorded that the number of clients undergoing rehabilitation in 2021 was 256, with 218 at severe levels, 36 at moderate levels, and 2 at mild levels, then 188 clients had completed rehabilitation. This study aimed to describe family and social environment factors to clients on drug abuse. This was descriptive research in that number of samples was 75 respondents selected by purposive sampling. The results revealed that most of the clients had inappropriate family and social environments. The former clients are encouraged to maintain proper relationships with their family and social life to avoid the potential opportunity for drug abuse. Furthermore, families are suggested to support and deliver more attention to clients who had run the rehabilitation process.